RETHINKING TEACHING AND LEARNING LANGUAGE IN THE NEW ERA: LESSONS FROM THE COVID-19 PANDEMIC IN TANZANIA - Upor, Rose Acen (LLT Journal: A Journal on Language and Language Teaching, 2021)
This study examines the language teaching and learning experiences in Tanzania that were prompted in response to the impact of COVID-19 pandemic-related school closures. Crucial to the study was determining how students’ and teachers’ coped with language teaching and learning and determining technological resources and their usefulness in language teaching and learning.A total of 127 students (74 female, 53 male) and 33 teachers participated in the study. The study revealed that the reception of educational broadcasting was low among the participants while reliance on mobile learning increased, the participants faced challenges when they attempted to cope with the shift to technology-based formats for language teaching and learning, and students were not fully able to develop the autonomy of learning on their own partly due to the unpreparedness for the shift to technology-based learning.Overall, the results confirm that web resources, SNS, and applications are rapidly becoming a resource for native speaker input for students learning English in foreign language learning contexts.